ANALYSIS AND FEATURES OF TRAFFIC MONITORING SOFTWARE - LEMESHKO, ANDRII; ANTONENKO АRTEM; TSVIK, OLEKSANDR (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The article discusses the main capabilities of traffic control programs. Sending too many Internet connection packets can result in heavy Internet traffic, which can lead to bottlenecks or network congestion. Meanwhile, operations between communication devices are also affected and slowed down. The main problem is that the growth of Internet traffic increases dramatically, and on the other hand, the Internet connection always has a finite bandwidth for data flow and can only support a certain number of packets at a time. Sending too many packets at once over an Internet connection is difficult because sending too many packets at once can lead to heavy Internet traffic that can become a bottleneck or cause network congestion. Meanwhile, transactions between communication devices are also affected and slowed down, which ultimately leads to Internet congestion and network service degradation. Effective congestion management is one of the most important issues in managing Internet traffic. The new algorithmic congestion prevention model will improve performance and network utilization by making TCP a more flexible and efficient protocol with a new preemptive approach. Traffic control programs are the primary application of a computer engineer. The entire world is interconnected by a vast network of routers, switches, servers, and consumers, and so many devices and packets need to be controlled. That is why the basic principle of traffic control was created. Thanks to such programs, there is a stable traffic and network. The future of today’s Internet is the adaptation of cloud computing, 3D technologies, the Internet of Things, global communication, distributed computing, wireless media, and high-definition multimedia broadcasting over the Internet. To manage sustainable and efficient Internet traffic, a systematic approach to planning, testing, and maintaining its behavioral mechanism is desirable to avoid network congestion and ensure uninterrupted data transmission. Effective congestion management is one of the most important problems of internet traffic management efficiency that needs to be solved. The main way to solve the problem is to use traffic control programs. Effective means that the control mechanism must also ensure the proper level of use of network resources, which is a fundamental condition for ensuring the profitability of work. It was found that the reason for the use of traffic control is the increase in the use of Internet resources - therefore, the use of programs is necessary for successful traffic control.